From Nature to Laboratory: The Impact of Leilem Leaves’ Ethanol Extract on Pancreatic Lipase Enzyme Activity - Siringo-Ringo, Aurian Fricilia; Fatimawali, Fatimawali; Bodhi, Widdhi; Manampiring, Aaltje E.; Kepel, Billy J.; Budiarso, Fone D.H. (Graha Primera Saintifika, 2024)
For many years, there have been theories on the possibility of preventing or delaying type 2 Diabetes Mellitus by altering some of its risk factors. Drugs that combat obesity have recently been researched concerning the prevention of type 2 Diabetes Mellitus. Inhibition of the digestive enzyme pancreatic lipase is a potential therapeutic strategy in treating and managing chronic diseases such as diabetes and obesity. Plants containing bioactive compounds are identified as potential sources of pancreatic lipase enzyme inhibitors. The use of natural compounds in inhibiting pancreatic lipase enzyme activity is considered to have more potential due to low toxicity and side effects. This study aims to determine the potential and activity effect of ethanol extract of leilem leaves on inhibiting pancreatic lipase enzyme. This study is a laboratory experimental study, the method of measuring lipase inhibition potential was performed using porcine lipase and PNPB with several modifications and using Orlistat as a positive control. Readings were taken using an ELISA reader at a wavelength of 405 nm. The data were then processed to obtain the IC50 value and relative potency. The results of in vitro studies have shown the potential of leilem leaf extract to inhibit pancreatic lipase enzyme activity. Qualitatively, the results showed that leilem leaf extract contains secondary metabolite compounds such as Alkaloids, Flavonoids, Tannins, Saponins, Steroids, and Terpenoids. Quantitatively, the results showed that the ethanol extract of leilem leaves had an absorbance value at the lowest concentration of 1.346 ± 0.53 and 0.709 ± 0.29 for the highest concentration. The IC50 result obtained was 137.89 μg/mL while the IC50 value of the positive control Orlistat was 77.022 μg/mL. Ethanol extract of leilem leaves (Clerodendrum minahassae Teijsm. & Binn) has a potential value of 0.558.